2015
DOI: 10.1590/0004-282x20150097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on nitrergic neurons in human striatum and subthalamic nucleus

Abstract: Nitric oxide (NO) is a major neurotransmitter associated with motor control in basal ganglia. Movement disorders, as essential tremor and Parkinson's disease, are more prevalent on aged individuals. We investigated the effects of aging on neuronal density and diameter/area of nitrergic neurons in samples of striatum (caudate and putamen) and subthalamic nucleus of 20 human brains from normal subjects, stained by histochemistry for NADPH-diaphorase and immunohistochemistry for neuronal NO synthase. Our data sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous studies did not find age‐related telomere attrition in human neuronal and glial cells across the adult age range in healthy controls but identified significantly shorter telomeres in glial cells compared with neurons (Tomita et al, 2018 ). Stereology studies consistently reported decreasing number of oligodendrocytes but not neurons with advancing age in the human neocortex (Fabricius et al, 2013 ; Pelvig et al, 2008 ), striatum and putamen (dos Santos‐Lobato et al, 2015 ; Selden et al, 1994 ). Similarly, changes in cell‐type‐specific gene expression did not indicate a decrease in neuronal markers with age (Soreq et al, 2017 ).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies did not find age‐related telomere attrition in human neuronal and glial cells across the adult age range in healthy controls but identified significantly shorter telomeres in glial cells compared with neurons (Tomita et al, 2018 ). Stereology studies consistently reported decreasing number of oligodendrocytes but not neurons with advancing age in the human neocortex (Fabricius et al, 2013 ; Pelvig et al, 2008 ), striatum and putamen (dos Santos‐Lobato et al, 2015 ; Selden et al, 1994 ). Similarly, changes in cell‐type‐specific gene expression did not indicate a decrease in neuronal markers with age (Soreq et al, 2017 ).…”
Section: Discussionmentioning
confidence: 98%